(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of this study was to separate phenol from Bio-Oil obtained from the pyrolysis of agricultural wastes (BAW). The BAW was obtained in one step catalytic pyrolysis in which temperature of the reactor was kept at 30°C and then increased up to 900°C. After pyrolysis, the BAW was distillated and analyzed by Gas chromatography and Mass spectrometry (GC-MS) technique and comprehensive two-dimensional gas chromatography with time-of-flight mass spectrometry detection (GC × GCTOFMS) Where BAW showed the presence of more than 120 other important compounds and phenol. After detection, phenol was separated by solvent extraction method, where Ethyl ether (C4H10O), Caustic soda (NaOH) and Hydrochloric acid (HCl) were used to separate phenol from BAW and then Nuclear magnetic resonance spectroscopy (NMR) was done to confirm the recovery of phenol.